Adsorption of new hydrophobic polyacrylamide on the calcite surface. Issue 38 (31st May 2017) - Wang, Shibin; Li, Geng; Li, Yang; Guo, Jianchun; Zhou, Siyan; Yong, Sun; Pan, Baofeng; Bai, Baojun
ABSTRACT: A hydrophobic polyacrylamide (HPAM) was synthesized by aqueous free‐radical chain polymerization to understand the adsorption action of the polymer on the calcite during operating stimulation. The polymer was designed as acrylamide (AM)/2‐acrylamide‐2‐methylpropanesulfonic acid (AMPS)/2‐methacryloyloxyethyl 12‐alkyl dimethyl ammonium bromide (MADA). The structure of the polymer was characterized by Fourier transform infrared spectroscopy. The adsorption properties of the polyacrylamide onto pure calcite was investigated. When we compared the ζ potentials of the calcite particles in the presence and absence of HPAM, the adsorbed amount was affected by different factors, and the adsorption behaviors were examined to determine the adsorption layer. The results of the ζ potential measurements indicated that the particles were negatively charged between pHs of 6 and 12, and the presence of HPAM did not reverse that. Equilibrium adsorption studies showed that the adsorbed amount was affected by the concentration of HPAM, liquid‐to‐solid ratio, calcite particle size, concentration of background ions, and temperature, which were related the adsorption behaviors of HPAM. Hydrogen bonds between HPAM and calcite were important because the adsorbed amount was significantly reduced when the hydrogen bonds were broken by urea. It is necessary to develop a more active reagent that can break the hydrogen bonds and improve the effect of hydraulic fracturing. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45314. Abstract :